Pembuatan Produk Ring Matahari dari Pelat ASTM A36 Menggunakan Plasma Cutting OXYTOOM 20 HPC - Nurbaiti Nurbaiti; Hendri Van Hoten; Candra Nico (MAJALAH TEKNIK SIMES, 2021)
Nowadays, Machine tools are equipped computer system, example: CNC plasma cutting machine. Computer Numerically Controlled plasma cutting is used to cut various types of metal, plate and other materials that it has good accuracy which uses heat obtained from a high concentration laser beam where the depth level is adjusted according to the thickness of the plate to be cut. One of the products is Sun Ring. Material to make this component is steel plate ASTM A36 which the thickness is 1 mm. The step to make this product is design that it help of Autocad software, Magic Logotag and Magic Tool. Result from cutting process are diameter 30.4 mm inner, 37.4 mm outer, 9.4 fin length and 3.8 mm fin width. Dimension drawing in Autocad software is bigger than workpiece size because it cut material (steel plate ASTM A36) quickly which it cause insignificant shift. Final process of this product is hone to get the actual dimension